Pengaruh Customer Journey dalam Usaha Spa di Ok Spa Kota Padang terhadap Kepuasan Pelanggan - Aisya Shabrina; Rahmiati Rahmiati (Lembaga Yasin AlSys, 2025)
The growth of the spa industry in Padang City demands optimal customer journey management to enhance customer satisfaction and strengthen business competitiveness. This study aims to describe the management of the customer journey at Ok Spa, analyze its effect on customer satisfaction, and measure the contribution of the customer journey to overall customer satisfaction at Ok Spa, Padang. A quantitative approach with an associative strategy was employed. The sample consisted of 42 respondents, and data were collected through questionnaires and analyzed using SPSS version 25. The results show that customer journey management at Ok Spa is categorized as excellent, with an average score of 4.31, while customer satisfaction is also rated very high with an average score of 4.41. Regression analysis indicates that the customer journey has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.349. The correlation coefficient of 0.608 indicates a strong positive relationship between the two variables. However, the contribution of the customer journey to customer satisfaction is only 37%, suggesting that other factors also influence overall customer satisfaction. These findings underscore the importance of managing the customer experience comprehensively at every interaction stage from pre-visit to post-service to foster customer loyalty and support the sustainability of spa businesses in Padang City.